Achieve with accountability - Evans, Mike (WILEY, 2017)
Achieve with Accountability presents a recipe for awakening the whatever it takes attitude to achieve what matters most to individuals, teams and organizations. Discover how to transform accountability into a positive, engaging and forward looking experience that will secure your position in the new world of work. Learn how to kick-start a revolution that will blast your team or organization to new heights of success. We are in a brawl with no rules, where the fast, flexible and agile will eat and spit out the slow, over-thinking and complacent